The beneficial prognostic value of hemoconcentration is negatively affected by hyponatremia in acute decompensated heart failure: Data from the Korean Heart Failure (KorHF) Registry. Issue 5 (May 2017) - Oh, Jaewon; Kang, Seok-Min; Kim, In-Cheol; Han, Seongwoo; Yoo, Byung-Su; Choi, Dong-Ju; Kim, Jae-Joong; Jeon, Eun-Seok; Cho, Myeong-Chan; Oh, Byung-Hee; Chae, Shung Chull; Lee, Myung-Mook; et al.
Abstract: Background: Hemoconcentration (HC) is associated with reduced mortality, whereas hyponatremia (HN) has been associated with an increased risk of adverse outcomes in patients with acute decompensated heart failure (ADHF). We sought to determine if the presence of HN influences the beneficial prognostic value of HC in ADHF patients. Methods: We analyzed 2046 ADHF patients from the Korean Heart Failure Registry. We defined HC as an increased hemoglobin level from admission to discharge, and HN as sodium <135 mmol/L at admission. Our primary composite endpoint was all-cause mortality and/or HF re-hospitalization. Results: Overall, HC occurred in 889 (43.5%) patients and HN was observed in 418 patients (20.4%). HC offered higher 2-year event-free survival in patients without HN (73.2% vs. 63.1% for no-HC, log-rank p < 0.001), but not in patients with HN (54.2% vs. 58.7% for no-HC, log-rank p = 0.879, p for interaction = 0.003). In a multiple Cox proportional hazard analysis, HC without HN conferred a significant event-free survival benefit (hazard ratio: 0.703, 95% confidence interval 0.542–0.912, p = 0.008) over no-HC with HN. Conclusions: Only HC occurring in ADHF without HN was associated with improved clinical outcomes. These results provide further support for the importance of HN as a challenging therapeutic target in ADHF patients.